Evaporative controls on Antarctic precipitation: an ECHAM6 model study using innovative water tracer diagnostics - Gao, Qinggang; Sime, Louise C; McLaren, Alison J; Bracegirdle, Thomas J; Capron, Emilie; Rhodes, Rachael H; Steen-Larsen, Hans Christian; Shi, Xiaoxu; Werner, Martin (The Cryosphere, 2024)
Improving our understanding of the controls on Antarctic precipitation is critical for gaining insights into past and future polar and global environmental changes. Here we develop innovative water tracing diagnostics in the atmospheric general circulation model ECHAM6. These tracers provide new detailed information on moisture source locations and properties of Antarctic precipitation. In the preindustrial simulation, annual mean Antarctic precipitation originating from the open ocean has a source latitude range of 49–35◦ S, a source sea surface temperature range of 9.8– 16.3 ◦ C, a source 2 m relative humidity range of 75.6 %– 83.3%, and a source 10m wind velocity (vel10) range of 10.1 to 11.3ms−1. These results are consistent with estimates from existing literature. Central Antarctic precipitation is sourced from more equator-ward (distant) sources via elevated transport pathways compared to coastal Antarctic precipitation. This has been attributed to a moist isentropic framework; i.e. poleward vapour transport tends to follow constant equivalent potential temperature. However, we find notable deviations from this tendency especially in the lower troposphere, likely due to radiative cooling. Heavy precipitation is sourced by longer-range moisture transport: it comes from 2.9◦ (300 km, averaged over Antarctica) more equator-ward (distant) sources compared to the rest of precipitation. Precipitation during negative phases of the Southern Annular Mode (SAM) also comes from more equator-ward moisture sources (by 2.4◦, averaged over Antarctica) compared to precipitation during positive SAM phases, likely due to amplified planetary waves during negative SAM phases. Moreover, source vel10 of annual mean precipitation is on average 2.1 m s−1 higher than annual mean vel10 at moisture source locations from which the precipitation originates. This shows that the evaporation of moisture driving Antarctic precipitation occurs under windier conditions than average. We quantified this dynamic control of Southern Ocean ...